Complete coding sequence and phylogenetic analyses of very virulent infectious bursal disease virus isolate of Malaysia - Liew, Pit Sze; Omar, Abdul Rahman; Ideris, Aini; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A complete nucleotide (nt) coding sequence of infectious bursal disease virus (IBDV) isolate of Malaysia (UPM04190) was determined. In segment A, 3260 nt was identified, consisting of 2 overlapping open reading frame, predicted to be the VP5 of 465 nt with 154 amino acids and the polyprotein of 3039 nt with 1012 amino acids. In segment B, 2825 nt was obtained and consisted one open reading frame with 2640 nt predicted to be the 879 amino acids of VP1. Comparison of the deduced amino acids revealed 8 unique amino acids which were conserved only in UPM04190. Of all these amino acids, 3 were found in VP1, 3 were in VP2, and 2 were in VP5. The overall branching pattern of the phylogenetic trees revealed a similar pattern. Taken together, nt sequence and phylogenetic analyses revealed and suggested that our local isolate UPM04190 share a high homology with the very virulent strains. Analysis of the IBDV nt and amino acid sequence are best targeted at both genomes.